Analisis Hubungan Corporate Social Performance (Csp) Terhadap Kinerja Keuangan Bank Syariah Yang Terdaftar Di Otoritas Jasa Keuangan (Ojk) Tahun 2013-2015 - Wirawan, Wina Permatasari, Dra. Wuryaningsih Dwi Lestari, M.M (2017)
ABSTRACT This study aimed to analyze the relationship between Corporate Social Performance (CSP) on the financial performance of Islamic banks listed in the Otoritas Jasa Keuangan (OJK) in 2013-2015. Samples taken as many as 11 Islamic banking by using data analysis techniques multiple linear regression test. Based on the results of the research analysis can be known from the eleventh ratios there are only four ratios that affect the financial performance that is of variable Contribution to Economic Development (KPE) is the ratio of intensity function Agency (AR), the variable Contribution to Society (KKM) is the ratio of zakat ( ZR) and the variable Contribution To Stakeholders (KUS) there are two ratios that affect the ratio Kesejahterahan Mudharib (KM) and the ratio Kesejahterahan Wadi'ah Holder (KPW). Islamic Banking needs to maintain the value of the ratio in Corporate Social Performance (CSP), which have an influence on financial performance. Key words: Corporate Social Performance (CSP), financial performance, Islamic Bank.